The Influence of Scientific Independence towards Students’ Content Analysis and Science Process Skills on Cell Metabolism Topic (Jurnal Pendidikan IPA Indonesia, 2018)
Students commonly judge that cell metabolism topic is arduous since they only listen to their teacher and memorizing concept without a deep comprehension. Other than that, a direct explanation could not enhance the students’ science process skills. Thus, this research intended to analyze the differences of the content-analysis and science process skills between the students experiencing a learning that oriented to scientific independence (experimental class) and those joining a direct learning (control class). The materials taught in both classes were cell metabolism. This study employed the quantitative of the quasi-experimental method. The research object was the students learning Biology. The students joining a scientific independence-based class were able to answer questions requiring analytical thinking. The relationship of the students’ scientific independence towards the content analysis and science process skills was seen on the test. Based upon the statistical data analysis, the correlation significance was 0,0380,05. Therefore, it concluded that there was a very significant correlation between the students’ scientific independence towards the content analysis and science process skills.